MINERALIZATION CHARACTERISTICS OF KIARAPAYUNG, CIBALIUNG DISTRICT, PANDEGLANG, BANTEN - Widyariestha, Mira; Rosana, Mega Fatimah; Haryanto, Iyan; Kurniawan, Andi (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
PT Cibaliung Tbk is one of active underground gold mining in West Java. The mineralization type is Au-Ag adularia-sericite low sulphidation (Angeles et al, 2002). Study area is located southeastward from main veins of Cibaliung, administratively in Kiarapayung village, Cibaliung District, Pandeglang, Banten. From previous study it is known that acid alteration typical of high sulphidation deposit also occurred in study area. This research aim to observe the characteristics of mineralization in study area, comprising of its occurrence, trend, and ore minerals present. This research use field observation and ore microscopy as main method to identify mineralization characteristics. Mineralization occurred in the field as quartz and silica veins with various textures; vuggy quartz; and silica-pyrite replacement bodies. Most veins have NW-SE trend, similar to trends of major faults in research area. Vuggy quartz and replacement zones distribution also found restricted to geological structures. Pyrite distribution in wallrock also showed trend that associated with geological structures. Textural observation with binocular microscope in veins and replacement zone showed rock brecciation process before ore-bearing alteration. Ore minerals present are pyrite and chalcopyrite with minor galena and chalcocite. Mineralization characteristics indicate there is low sulphidation and high sulphidation type mineralization in study area. Both mineralization are strongly influenced by geological structures.Keywords: mineralization, veins, vuggy quartz, texture, structural control.